2018
DOI: 10.1111/ced.13329
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome with multiple lentigines and associated craniosynostosis

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Pathogenic, activating variants in genes of the fibroblast growth receptor (FGFR) pathway are the major cause of syndromic craniosynostoses, with variants in FGFR2 and FGFR3 causing almost half of these cases (Cunningham et al, 2007;Wilkie et al, 2017). However, craniosynostosis has recently been recognized to be associated with multiple RASopathies including CFCS, NS, NSML, and Noonan-like with loose anagen hair (Bertola et al, 2017;McDonald et al, 2018;Takenouchi et al, 2014;Ueda et al, 2017). The etiology of RASopathyassociated craniosynostosis is hypothesized to be related to the intersection of the RAS/MAPK and FGFR signaling pathways (Addissie et al, 2015;Takenouchi et al, 2014).…”
mentioning
confidence: 99%
“…Pathogenic, activating variants in genes of the fibroblast growth receptor (FGFR) pathway are the major cause of syndromic craniosynostoses, with variants in FGFR2 and FGFR3 causing almost half of these cases (Cunningham et al, 2007;Wilkie et al, 2017). However, craniosynostosis has recently been recognized to be associated with multiple RASopathies including CFCS, NS, NSML, and Noonan-like with loose anagen hair (Bertola et al, 2017;McDonald et al, 2018;Takenouchi et al, 2014;Ueda et al, 2017). The etiology of RASopathyassociated craniosynostosis is hypothesized to be related to the intersection of the RAS/MAPK and FGFR signaling pathways (Addissie et al, 2015;Takenouchi et al, 2014).…”
mentioning
confidence: 99%
“…Half of them correspond to NS, seven to CFCS, and only two fit with NSML diagnosis (including present case). The other patient with NSML and craniosynostosis was described recently by McDonald et al (). Exome sequencing analysis of that patient revealed a heterozygous pathogenic variant in PTPN11 (p.R498W), previously reported in association with NSML (Digilio et al, ; Sarkozy, Conti, et al, ; Sarkozy, Obregon, et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, different studies have shown consistent association between craniosynostosis and NS patients with SHOC2 , KRAS , and PTPN11 pathogenic variants (Addissie et al, ; Takenouchi et al, ; Ueda, Yaoita, Niihori, Aoki, & Okamoto, ), and CFCS patients with KRAS and BRAF pathogenic variants (Ueda et al, ). Recently, the first patient with NSML ( PTPN11 pathogenic variant) and craniosynostosis was reported (McDonald et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sagittal craniosynostosis was observed in NS1096. Craniosynostosis has been reported in patients with Noonan syndrome ( PTPN11 and KRAS ), Noonan syndrome with multiple lentigines ( PTPN11 and RAF1 ), Noonan syndrome‐like disorder with loose anagen hair ( SHOC2 and PPP1CB ), and CFC syndrome ( BRAF and KRAS ) (Addissie et al, 2015; Bertola et al, 2017; Kratz et al, 2009; McDonald et al, 2018; Rodriguez et al, 2019; Takenouchi et al, 2014; Ueda et al, 2017). To our best knowledge, craniosynostosis has not been reported in CS patients with HRAS variants.…”
Section: Discussionmentioning
confidence: 99%